Soil cover vegetation analysis on soil physical properties at PT Cibaliung Tunggal Plantation Cibaliung I Rokan Hilir regency Riau province - Muhammad Nurkolis Baru Bara; Ingrid Ovie Yosephine (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Ground cover vegetation plays a crucial role in maintaining soil quality and preventing degradation by altering soil physical properties. This study aimed to analyze differences in soil physical properties, particularly bulk density, porosity, and water content, in areas covered with different types of ground cover vegetation at PT Cibaliung Tunggal Plantation, Kebun Cibaliung I, Riau. The method used was a field survey with purposive sampling of soil at two depths, namely 0–10 cm and 10–20 cm. The observation sites included three vegetation conditions: fern (Nephrolepis biserrata), crocodile-nest grass (Ottochloa nodosa), and bare land. Laboratory analysis indicated that vegetation significantly improved soil physical properties. The lowest bulk density values were found in areas with Ottochloa nodosa vegetation (0.35–0.78 g/cm³), whereas the highest values were found in areas without vegetation (1.35–1.45 g/cm³). All locations exhibited “very good” porosity criteria (>20%), with the highest values in Ottochloa nodosa areas reaching 88–95%. In terms of water retention, vegetated areas demonstrated greater capacity than bare areas; the highest water content was recorded in O. nodosa areas (81–202%), whereas bare areas exhibited water content ranging from 18–21%. This study concluded that using ground cover vegetation can significantly reduce soil density and increase porosity and water storage capacity, thereby supporting sustainable land productivity, especially during the oil palm replanting period. These findings highlight Ottochloa nodosa's superior performance in optimizing soil moisture and structure, suggesting that plantation managers should prioritize its conservation to enhance long-term soil sustainability.